2018
DOI: 10.3390/met8020107
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Metal Reagent-Assisted Synthesis of Monodisperse Iron Oxide Nanostructures

Abstract: Abstract:The solvothermal decomposition of iron complexes using the heat-up process enables monodisperse Fe 3 O 4 nanoparticle synthesis. Here, we demonstrate that the high reduction potential capability of alkaline metal reagents in the reductive environment allows for pure magnetite phase formation at 200 • C, which is lower than that of typical synthetic method and offers highly crystalline superparamagnetic and ferrimagnetic nanostructures with the ability to control uniformity including spherical and cubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Thermal decomposition of iron complexes at high temperature in high-boiling point organic solvents has proven to be an effective method to generate Fe 3 O 4 nanospheres with sizes ranging from 4 to 30 nm [54][55][56][57][58]. Sun et al reported the thermal decomposition of Fe(acac) 3 in phenyl ether (boiling point: 260 • C) at 265 • C to synthesize monodisperse 4 nm Fe 3 O 4 SNPs [54].…”
Section: Fe 3 O 4 Spherical Nanoparticles (Snps)mentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal decomposition of iron complexes at high temperature in high-boiling point organic solvents has proven to be an effective method to generate Fe 3 O 4 nanospheres with sizes ranging from 4 to 30 nm [54][55][56][57][58]. Sun et al reported the thermal decomposition of Fe(acac) 3 in phenyl ether (boiling point: 260 • C) at 265 • C to synthesize monodisperse 4 nm Fe 3 O 4 SNPs [54].…”
Section: Fe 3 O 4 Spherical Nanoparticles (Snps)mentioning
confidence: 99%
“…Therefore, precisely controlling the temperature of the reaction and a powerful heating process represent a technical challenge for large-scale production. Later, Lee and coworkers successfully lowered the reflux temperature to 200 • C using alkaline metal reagents to assist with the reduction of iron precursors [58]. In the presence of Mg(acetate) 2 , monodisperse Fe 3 O 4 SNPs with sizes of 8, 11, 15, and 18 nm were prepared.…”
Section: Fe 3 O 4 Spherical Nanoparticles (Snps)mentioning
confidence: 99%
See 1 more Smart Citation
“…The main obstacle of this procedure is the control of nanoparticle size and polydispersity. One of the major advantages is the opportunity to synthesize composite materials [72][73][74][75]. While normal micelles form in an aqueous medium, reverse micelles form in hydrophobic media [68,70].…”
Section: Thermal Decomposition and Reductionmentioning
confidence: 99%
“…According to their results, Nb 2 O 5 synthesized though the sol-gel method had orthorhombic symmetry and exhibited high pressure stability. Lee et al [10] demonstrated a facile method to synthesize enhanced pure phase and monodisperse magnetite nanoparticles and nanocubes. The high reduction potential capability of alkaline metal reagents in the reductive environment allowed formation of a pure magnetite phase.…”
Section: Contributionsmentioning
confidence: 99%